2022
DOI: 10.1038/s41467-021-27655-0
|View full text |Cite
|
Sign up to set email alerts
|

Helical structure motifs made searchable for functional peptide design

Abstract: The systematic design of functional peptides has technological and therapeutic applications. However, there is a need for pattern-based search engines that help locate desired functional motifs in primary sequences regardless of their evolutionary conservation. Existing databases such as The Protein Secondary Structure database (PSS) no longer serves the community, while the Dictionary of Protein Secondary Structure (DSSP) annotates the secondary structures when tertiary structures of proteins are provided. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…While the hinge motion is thus important, several studies provide substantial evidence supporting the feasibility of designing and synthesizing peptide sequences that leverage functional amino acid sequences derived from proteins. 64–66 For example, Fowler et al (2021) 67 demonstrated selective P i adsorption and controlled desorption using a protein-derived P i -binding peptide sequence approximately 37× smaller than the PBP tested in our study. Immobilization of such peptide sequences and testing their P i binding potential in a range of conditions relative to water/wastewater is important moving forward to further evaluate the adsorbent's abilities relative to other adsorbents.…”
Section: Resultsmentioning
confidence: 49%
“…While the hinge motion is thus important, several studies provide substantial evidence supporting the feasibility of designing and synthesizing peptide sequences that leverage functional amino acid sequences derived from proteins. 64–66 For example, Fowler et al (2021) 67 demonstrated selective P i adsorption and controlled desorption using a protein-derived P i -binding peptide sequence approximately 37× smaller than the PBP tested in our study. Immobilization of such peptide sequences and testing their P i binding potential in a range of conditions relative to water/wastewater is important moving forward to further evaluate the adsorbent's abilities relative to other adsorbents.…”
Section: Resultsmentioning
confidence: 49%
“…Moreover, artificial intelligence and machine learning may offer an inverse (but complementary) approach, through which full-length protein structures can be analysed to identify new peptides. For example, secondary structures of nearly 2 million protein helices have been compared by a pattern-based search engine to identify and locate antimicrobial motifs and to provide design rules to control protein-protein interactions 221 . Similarly, a combination of machine learning and multivariate outlier detection models has helped to discover new non-haemolytic peptides and provide de novo design guidelines 222 .…”
Section: Discussionmentioning
confidence: 99%
“…The process of motif identification and extraction is slow and can be highly accelerated through the use of computational methods. For example, Tsai et al [29] recently created TP-DB (therapeutic peptide design database) that allows the users to search helical motifs that match a given sequence pattern. Their pattern-specific search engine is based on features derived from nearly 1.7 million helical structures extracted from PDB.…”
Section: Structure-guided Design Of Functional Peptidesmentioning
confidence: 99%